The Relationship Of Characteristics And Work Attitude With Low Back Pain Complaints On Nurse Of Regional Public Hospital Petala Bumi Riau Province 2022: Hubungan Karakteristik Dan Sikap Kerja Dengan Keluhan Low Back Pain Pada Perawat Rumah Sakit Umum Daerah Petala Bumi Provinsi Riau Tahun 2022 - Muhammad Ade Setiawan; Herniwanti Herniwanti; Mitra Mitra; Riri Maharani; Ikhtiyaruddin Ikhtiyaruddin (Badnur Medisa Group, 2022)
Low Back Pain is one of the occupational diseases that often occurs and can hit all people of the same sex age and work, medical facilities especially hospi-tals are defined as the environment in which ergonomics-related activities take place including lifting push pulling and carrying objects and handling patients. This study aims to determine the The Relationship Of Characteristics And Work Attitude With Low Back Pain Complaints On Nurse Of Regional Public Hospital Petala Bumi Riau Province 2022. The research method used is quantitative research with a Cross Sectional research design. The number of samples in this study consist-ed of 59 nurses in the inpatient installation room, ICU and IGD. Sampling using the Total Sampling technique. Data collection using questionnaires, Data analysis uni-variately and bivariately with chi-square test with a confidence level of 95%. The results of the Univariate analysis were 27 (45.8%) respondents who experienced Low Back Pain and there were 32 (54.2%) respondents who did not experience Low Back Pain. The results of the study obtained there were 4 variables related to age with value (P-value = 0.033) with POR = 3.750, gender with value (P-value = 0.034) with POR = 4.472, length of work with (p Value = 0.032) with POR = 3.717, and work attitude with value (P-value = 0.030) with POR = 6.548 and 1 unrelated variable, namely the length of work with the value (P-value = 1,000) with POR = 0.821 with complaints of Low Back Pain. It is recommended to the Petala Bumi Regional Public Hospital, Riau Province, to provide occupational safety and health counseling related to work ergonomics to nurses and direct them to stretch every 5-10 minutes.